Energy pricing and supply for groundwater demand management: lessons from Mexican agriculture - Scott, Christopher A.; Shah, Tushaar; Buechler, Stephanie J. (International Water Management Institute, 2003)
Research highlight based on a paper titled "Energy pricing and supply for groundwater demand management: Lessons from Mexican agriculture",